Niqab in Indonesia: Identity and Nationalism of the Female Students in Palopo - Abdul Pirol; Aswan Aswan (UIN Sunan Gunung Djati Bandung, 2021)
This research discusses the politics of identity that are increasingly strengthening in the public sphere. This phenomenon grows through the religious sentiment circulated massively on social media and is also evident in dress and daily behavior. This article wants to see: (1) the extent to which the identity of female students that wearing niqab influences the national insight, (2) how their perspectives and attitudes in national and state life. As a result, the sentiment of niqab female students' identity grew more vital in the public sphere. It is directly proportional to their low acceptance of government leaders of different religions. The government role is also considered lacking in helping them to overcome the life problems they face. Interestingly, the position of the Pancasila in the group gaining acceptance is relatively high. The primary data of this study through a questionnaire with the techniques of purposive sampling of 30 female students that wearing the niqab from various religious organisations spread across many campuses in the City of Palopo.